End-User Highlighted: featuring tailorable systems development - Correa, Claiton Marques; Silveira, Milene Selbach (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2021: Anais do XX Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2021)
Software varies in the domain and has different target users. Also, it is not possible to predict all users' requirements at the system development stage. This situation sheds light on the need to support end-users to adapt their applications to cope with new demands. End-User Development (EUD) is a research area that intents to permit end-users to perform activities beyond application usage. Such activities may involve software tailoring. Considering this, we aim to map the EUD towards supporting software with tailoring capabilities. To achieve this goal, we conducted a literature review using a snowballing procedure on the subject, and we found 42 studies in the time range 1997-2020. We analyzed the topic's development in terms of concepts, methodologies to building tailorable software, tools, and we treat issues and implications of tailorable systems development. Finally, we present future works to research and develop tailorable systems based on gaps and opportunities identified.